PENERAPAN MODEL BRAIN BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII PADA SISWA MTs/SMP - Iski, Nurul (Al-Khawarizmi, 2019)
Mathematical communication is very important in the process of learning mathematics. Through mathematical communication, students can organize their mathematical thinking in writing and communicate their understanding to others. However students mathematical communication skill are relatively low, so we need a learning model that can improve student’s mathematical communication skills by using brain based learning. The purpose of this research are  : (1) To determine the improvement of student’s mathematical communication skill after using Brain Based Learning Model. (2) To know the comparation between the student’s mathematical communication skill by using Brain Based Learning with convetional learning models. The research method used was a quasi-experimental design with pretest and posttest control group design. The result showed that : (1) The use of Brain Based Learning improves mathematical communication skill significantly. (2) Student’s mathematical communication skill by using Brain Based Learning were better that student’s mathematical communication skills by using conventional learning model.